Impact of overall government performance on post disaster crime rates - Antonio, Annie Carmeli G. (School of Economics, University of the Philippines Diliman, 2018)
The impacts of natural disasters can leave areas destroyed, leading to loss in lives, infrastructure, and livelihood. Being in the Pacific Ring of Fire, the Philippines is constantly hit by tropical cyclones. Its effects do not only affect economic and health outcomes but also social outcomes like index crime rates. Thus, we investigate the impact of over_all government performance on post_disaster crime rates. We aim to know the impact of government performance on crime rates after typhoon disasters, determine what elements of government performance significantly contribute to this impact, and discuss which crimes are associated with government performance after tropical cyclones. We analyze two models, first, a model on the effect of tropical cyclones on index crime rates, and second, a model on the effect of government performance on post-disaster index crime rates using fixed effects regression. The results show that crime victimization does increase in times of tropical cyclones because of changes in rainfall volume and the number of people affected, although it varies among each type of crime. These effects can also have medium_term and longterm impacts. The same goes for neighborhood fears as well, but on a greater extent. Although when controlling for overall government performance, it does not significantly affect the level of crime victimization and neighborhood fears across provinces. Future research regarding this work are recommended to use reported crime data and better government performance measure, and to measure data at the same level to avoid collinearity and disaggregation of data.